Intérêts et limites de la clinique psychanalytique de recherche sur les TIC en éducation - Jean-Luc Rinaudo (Recherches en Éducation)
The purpose of this paper is to show how the clinical approach with a psychoanalytical perspective can be applied to analyze the use of information and computer technology (ICT) in the field of education and teaching. In the first section of this paper, the characteristics of this approach will be elucidated. Then, we shall see how computer practices and educational practices, taken in their broader sense, can be understood through the prism of the myths and the desires that underlie them. With the help of an example from our research work, we shall study how computer practices in education combine psychological aspects around the concept of the negative and those of the construction or reinforcement of links, for both the group and its individuals. In conclusion, we shall point out the scope as well as the limitations of this approach to knowledge production.